Features of morphology and hydrology for spawning rivers at the northwestern coast of the Okhotsk Sea - Sergey F. Zolotukhin; Alexey N. Makhinov; Albina N. Kanzeparova (Известия ТИНРО, 2014)
At the northwestern coast of the Okhotsk Sea, pink salmon finds its spawning grounds both in big rivers (Uda, Okhota, and some other) and small streams because the size, slopes, and structure of alluvial sediments of the majority of local water bodies are suitable for the spawning. In small streams (< 20 km long), the pink salmon prefers to spawn in the simplest parts of beds, with linear channel sloped enough for bottom infiltration, but the chum salmon usually does not spawn there. These environments are rare for large rivers of this area which are more turbulized, with the beds often transformed by floods, strongly meandering, highly branched, and sometimes splitted to several channels; however, the largest and the most numerous spawning sites of pink and chum salmons are maintained in the latter case of splitted river-bed that is typical for lower parts of the biggest rivers, though other parts of these rivers are not preferable for their spawning because of high instability of the environments. The spawning grounds of chum salmon are more resistible against floods than the pink salmon ones: they form around either parafluvial (hyporheic) or ortofluvial springs. Generally, the areas with underwater springs preferable for the salmons spawning are more usual for big rivers with variable geomorphology, numerous tributaries, and extended multichannel parts.